2016
DOI: 10.4110/in.2016.16.5.286
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Viral Replication by Cellular Replicative Senescence

Abstract: Cellular replicative senescence is a major contributing factor to aging and to the development and progression of aging-associated diseases. In this study, we sought to determine viral replication efficiency of influenza virus (IFV) and Varicella Zoster Virus (VZV) infection in senescent cells. Primary human bronchial epithelial cells (HBE) or human dermal fibroblasts (HDF) were allowed to undergo numbers of passages to induce replicative senescence. Induction of replicative senescence in cells was validated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 34 publications
3
69
0
2
Order By: Relevance
“…Seasonal A/H3N2, B/Yamagata, B/Victoria clinical strains were obtained from Korea Bank for Pathogenic Viruses (KBPV) and influenza B/Malaysia/2506/04 (B/Victoria) strains were used. Virus titers were determined by standard plaque assay in MDCK cells with few modifications (Kim et al, 2016; Seong et al, 2016). Briefly, viral supernatants diluted in DMEM were added to MDCK cells in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Seasonal A/H3N2, B/Yamagata, B/Victoria clinical strains were obtained from Korea Bank for Pathogenic Viruses (KBPV) and influenza B/Malaysia/2506/04 (B/Victoria) strains were used. Virus titers were determined by standard plaque assay in MDCK cells with few modifications (Kim et al, 2016; Seong et al, 2016). Briefly, viral supernatants diluted in DMEM were added to MDCK cells in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The observation that SIRT1 expression was increased in different human cancers such as prostate cancer, colon cancer, and acute myeloid leukemia (14,16,38), where it inhibits apoptosis and senescence, suggests that SIRT1 inhibition may be useful in predicting which types of cancer would be amenable to oncolytic-virus treatment. Cellular replicative senescence has been described as a reprogramming of the cellular phenotype that facilitates increased viral replication, mainly due to impaired viral sensing and dampening of IFN induction by host cells (39). HDAC inhibition elicits a SASP response, due to chromatin remodeling, in the absence of DNA breaks (40).…”
Section: Discussionmentioning
confidence: 99%
“…Other viruses have developed mechanisms to overcome senescence and to evade anti-viral response, as reported for simian virus 40 [66] and human papillomavirus [67]. More recently, it has been shown that IFV and Varicella Zoster Virus display enhanced replication efficiency in senescent human bronchial epithelial cells as well as in senescent human dermal fibroblasts compared to non-senescent cells [68].…”
Section: Cellular Senescence and Response To Virusesmentioning
confidence: 99%
“…Mitochondrial fusion is generally required for intracellular proliferation of the viruses and evasion of the antiviral innate immune signaling, as demonstrated for the dengue virus infection mechanism [89]. In the case of dengue virus infection, cellular senescence seems to exert an anti-viral function [64] but other viruses, such as IFV, have evolved mechanisms to increase replication in senescent cells [68]. These observations illustrate that the behavior of different viruses in response to senescence can be different and that specific studies for each virus are needed.…”
Section: Cellular Senescence and Response To Virusesmentioning
confidence: 99%